2005
DOI: 10.1111/j.1399-3038.2005.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Mites in dust samples from mattress surfaces from single beds or cribs in the south Brazilian city of Londrina

Abstract: The aim of this study was to investigate the mite fauna in mattresses dust samples from cribs or beds in the south Brazilian city of Londrina, State of Parana. A total of 133 dust samples from upper and lower mattress surfaces, and bed frames were aspirated once from 38 dwellings (18 cribs and 21 beds), and one day nursery (six cribs). A total of 758 mite bodies were counted in slides: 233 (30.7%) from cribs and 525 (69.3%) from beds (p<0.001). House dust mites--mainly Dermatophagoides pteronyssinus, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…Similar mean concentrations of D. pteronyssinus (the highest in the fourth quarter) in the analogous material were observed in southern and northern Poland (Solarz, 1997; Aloszko et al., 2004). Much higher mean concentrations (500 and more mites per 1 g of dust) than in this paper were found in Brazil and Malaysia (Mariana et al., 2000; Silva et al., 2005).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Similar mean concentrations of D. pteronyssinus (the highest in the fourth quarter) in the analogous material were observed in southern and northern Poland (Solarz, 1997; Aloszko et al., 2004). Much higher mean concentrations (500 and more mites per 1 g of dust) than in this paper were found in Brazil and Malaysia (Mariana et al., 2000; Silva et al., 2005).…”
Section: Discussioncontrasting
confidence: 43%
“…Similar mean concentrations of D. pteronyssinus (the highest in the fourth quarter) in the analogous material were observed in southern and northern Poland (Solarz, 1997;Aloszko et al, 2004). Much higher mean concentrations (500 and more mites per 1 g of dust) than in this paper were found in Brazil and Malaysia (Mariana et al, 2000;Silva et al, 2005). Taking into consideration two species: D. farinae and D. pteronyssinus examined in north-western Poland, we observed that their highest mean concentrations occurred in the NH season, although the relative air humidity in the H season was slightly higher.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Higher dust mite allergen levels are associated with wool bedding and inner-spring mattresses. 67 Although mattresses are major reservoirs of mite allergen, studies have shown significantly higher levels of mite allergen 68,69 and mite bodies 70,71 in mattress bases (box springs) than in mattresses.…”
Section: Exposure To Dust Mite Allergensmentioning
confidence: 99%
“…It is important to better understand all aspects of allergen exposure before we classify them as a protective or sensitizing factor. With this in mind, this study aimed to investigate the two main respiratory allergens for our geographic area [ 24 27 ] and whether specific antibodies could be transferred through trans-placental and breastfeeding routes.…”
Section: Introductionmentioning
confidence: 99%